Mental health condition of caregivers affected metal health of burn injury patients. Issue 5 (30th January 2023) - Qin, Beibei; Li, Xi; Zhang, Han; Zhang, Cuina; Zhao, Linru
Abstract: The present study aimed to explore the association between mental health condition of caregivers and mental health of burn injury patients. Totally 300 burn injury patients and 300 caregivers were enrolled. These two cohorts of patients were randomly allocated to study group and control group (150 patients and 150 caregivers in each group). The mental health condition of patients and caregivers was evaluated both before and after psychological interventions. There was a significant reduction of the self‐rating depression scale (SDS) and self‐rating anxiety scale (SAS) of patients in the study group and control group after intervention (28.23 ± 4.98 vs 32.21 ± 5.01, P < 0.001; 28.18 ± 5.01 vs 31.18 ± 5.04, P < 0.001). The corresponding indexes of caregivers showed similar results before (SDS: 47.03 ± 4.41 vs 46.98 ± 4.39, P = 0.922; SAS: 47.01 ± 4.31 vs 46.93 ± 4.35, P = 0.873) and after intervention (21.76 ± 4.23 vs 38.98 ± 4.09, P < 0.001; SAS: 21.02 ± 4.09 vs 38.65 ± 4.04, P < 0.001). The SDS score of patients in study group was positively correlated with the SDS and SAS score of caregivers (r = 0.418 and 0.218, P = 0.003 and 0.012). The SAS score of patients in the study group was also positively correlated with the SDS and SAS scores of caregivers (r = 0.107 and 0.761, P = 0.029 and 0.018). Multiple linear regression showed that age, education and time of care per day were the independent variables associated with mental health condition of caregivers in the study group ( P < 0.05). Mental health condition of caregivers was closely related to the mental health of patients. Age, education and time of care per day were the independent variables associated with mental health condition of caregivers.